Production of gasoline from municipal solid waste via steam gasification, methanol synthesis, and Methanol-to-Gasoline technologies: A techno-economic assessment - Hamad AlMohamadi (AIMS Energy, 2021)
A techno-economic analysis of the process of producing gasoline via steam gasification of municipal solid waste (MSW) using dolomite catalysts, followed by a methanol synthesis and a methanol-to-gasoline process (SGMG) was conducted using an Aspen Plus model and an economic assessment. The process includes six steps: MSW pretreatment, steam gasification of MSW to produce syngas, gas purification through CO2 and acid gas removal, methanol synthesis using syngas, conversion of methanol to gasoline, and gasoline separation. The Aspen Plus model used to estimate the energy and mass balance for sizing the equipment assumed that 2000 dry metric tonnes of MSW per day would be processed. Capital investment required and operating costs of gasoline production were estimated based on the Aspen Plus model's mass and energy balance and an nth plant. The minimum selling price (MSP) of gasoline was calculated using the capital investment and operating costs of the process. The total capital investment of the process was estimated to be ＄148 million, with an annual operational cost of ＄56 million. The minimum selling price was determined at ＄2.40/gal for a 20-year project life. The sensitivity analysis showed that the cost of feedstock has a direct impact on the MSP of gasoline, and MSP could decrease to ＄1.55/gal if the owners of the plant received disposal fees. Increasing the gasoline yield to 0.125 kg of gasoline/kg of MSW decreased the MSP to ＄1.86/gal. The ash content in MSW played a vital role in estimating the MSP. If the ash content in the feedstock increased, the MSP increased owing to a decrease in the gasoline yield and an increase in the cost of operations.